The Irish schoolboy novel - O'NEILL, CIARAN (My University, 2009)
Ireland has its own set of much neglected schoolboy novels. Aside from James Joyce's seminal work, A Portrait of the Artist as a Young Man (1916), few have received any critical attention, due in many cases to small print runs. This article is an attempt to rescue the Irish schoolboy novel from its relative obscurity. Although the quality of some of the novels may well be debatable, they nevertheless provide us with a rare and valuable glimpse at the reality of school life for Irish boys in the nineteenth century.
PUBLISHED
Keywords: History; Ireland; The Irish Schoolboy Novel